Use of tire rubber residue in reinforced concrete pipes - Trentin, Thiago F.S. [UNESP]; Moraes, João C.B. [UNESP]; Melges, José L.P. [UNESP]; Akasaki, Jorge L. [UNESP]; Fugii, Ana P. [UNESP]; Tashima, Mauro M.; Camacho, Jefferson S. [UNESP] (Trans Tech Publications, 2016)
The concrete material has many advantages as high durability, low permeability, weather resistance and high compressive strength. These qualities have led its application to the rainwater collection since the pipes are usually buried, subject to compressive forces and exposed to the action of water. However, the concrete has some limitations, as, for example, low resistance to tensile stress, high self-weight, ease of cracking and brittle behavior in rupture. Thus, many materials are being studied in order to be used as a new concrete component seeking to minimize its disadvantages. One of them is the tire rubber residue. This residue is a fibrous material that takes a long time to decompose and increases the amount of trash in landfills; but, it may give a greater deformation capacity and also a more effective distribution of stresses to the concrete. Furthermore, the tire rubber residue can provide an increase in energy absorption and a decrease in the propagation of cracks in the hardened state. However several studies mention that the inclusion of the waste rubber into the concrete causes a decrease in mechanical strength to compression, a decrease in the workability of the mixtures and an increased content of entrained air. Therefore, an analysis of the structural behavior of four (4) reinforced concrete pipes was made: two (2) of them was molded without tire rubber residue and, the other two (2), with a quantity of residue equal to 20 kg per cubic meter of concrete. All the pipes had a nominal diameter of 600 mm and an effective length of 1500 mm; they were subject to the crushing test standardized by the Brazilian Association of Technical Standards - NBR 8890 (ABNT, 2007) which is similar to the European standard NBNEM 1616. The diametric displacements at the hub and at the spigot were monitored by the use of two dial gauge indicators. The applied force by a hydraulic jack was measured using a cell load. Finally, tests of water absorption using pieces of the tested pipes were performed, based on the recommendations of the NBR 8890 (ABNT, 2007).
Keywords: Crushing test; Reinforced concrete pipes; Sustainability; Tire rubber residue